2023
DOI: 10.1039/d3fo03261b
|View full text |Cite
|
Sign up to set email alerts
|

Unveiling the flavone-solubilizing effects of α-glucosyl rutin and hesperidin: probing structural differences through NMR and SAXS analyses

Kazunori Kadota,
Tero Kämäräinen,
Fumie Sakuma
et al.

Abstract: We are assessing flavone dissolution, by probing the interactions with Rutin-G and Hsp-G in aqueous solutions. Small-angle X-ray scattering and nuclear magnetic resonance analyses revealed that the solubilizing effect of Rutin-G was higher than that of Hsp-G.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 71 publications
0
1
0
Order By: Relevance
“…Our previous work showed that although we administrated this dose, rutin's concentration in the rats’ lung was only about 1.86 μg mL −1 (3 μmol L −1 ), 26 which may be because most of the rutin is excreted from the body as the original drug due to rutin's low solubility and bioavailability. 33,34 The animal dose of rutin is approximately 31.75 mg kg −1 d −1 for a human by converting it with A = k ( W 2/3 )/10 000 ( A , body surface area; k , a constant that varies with species; W , body weight). According to most of the rutin supplements on the market in the Dietary Supplement Label Database (), the recommended dietary dose ranges from 500 mg to 4 g per day, and it is feasible to reach this intake, but this dose only predicts the initial dose, and further study would optimize its therapeutic concentration in humans.…”
Section: Resultsmentioning
confidence: 99%
“…Our previous work showed that although we administrated this dose, rutin's concentration in the rats’ lung was only about 1.86 μg mL −1 (3 μmol L −1 ), 26 which may be because most of the rutin is excreted from the body as the original drug due to rutin's low solubility and bioavailability. 33,34 The animal dose of rutin is approximately 31.75 mg kg −1 d −1 for a human by converting it with A = k ( W 2/3 )/10 000 ( A , body surface area; k , a constant that varies with species; W , body weight). According to most of the rutin supplements on the market in the Dietary Supplement Label Database (), the recommended dietary dose ranges from 500 mg to 4 g per day, and it is feasible to reach this intake, but this dose only predicts the initial dose, and further study would optimize its therapeutic concentration in humans.…”
Section: Resultsmentioning
confidence: 99%